2012
DOI: 10.1080/10871209.2012.668610
|View full text |Cite
|
Sign up to set email alerts
|

Rural Inhabitant Perceptions of Sandhill Cranes in Wintering Areas of Northern Mexico

Abstract: Trends in the mid-continent population of sandhill cranes (Grus canadensis) indicate that the species is increasing. A large proportion of this population winters in northern Mexico where possible conflicts between local inhabitants and cranes can occur. We conducted interviews of 40 rural inhabitants living near wetlands used by cranes in three Mexican states. All interviewees had knowledge of cranes and were capable of describing them. The arrival of cranes affected 43% of interviewees. The negative effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
0
0
1
Order By: Relevance
“…Several studies have investigated the attitudes and perceptions of famers toward various species of cranes, including: the Brolga (Antigone rubicunda) and Australian Sarus Crane (Antigone gillae; Nevard et al 2018), Blue Crane (Anthropoides paradiseus; van Velden et al 2016), and Sandhill Crane (Antigone canadensis; Barceló et al 2012). Other studies have reported on the awareness, knowledge, and attitudes of communities toward the Whooping Crane (Grus americana; Lessard et al 2018), Black Crowned-Crane (Balearica pavonina; Gemeda et al 2016) and Indian Sarus Crane (Grus antigone antigone; Saiyed et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the attitudes and perceptions of famers toward various species of cranes, including: the Brolga (Antigone rubicunda) and Australian Sarus Crane (Antigone gillae; Nevard et al 2018), Blue Crane (Anthropoides paradiseus; van Velden et al 2016), and Sandhill Crane (Antigone canadensis; Barceló et al 2012). Other studies have reported on the awareness, knowledge, and attitudes of communities toward the Whooping Crane (Grus americana; Lessard et al 2018), Black Crowned-Crane (Balearica pavonina; Gemeda et al 2016) and Indian Sarus Crane (Grus antigone antigone; Saiyed et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…La Grulla gris es una especie poco estudiada en México, no obstante que se ha identificado un conflicto entre los campesinos (Barceló et al 2012) y las grullas debido a que se alimentan en los campos de cultivo durante el invierno. Y es paradójico que mientras se encuentra Bajo Protección Especial por la NOM-059-SEMARNAT-2010 (SEMARNAT 2010) se considera una especie cinegética de acuerdo a la Ley General de Vida Silvestre (SEMANAP 1999, Contreras et al 2001.…”
Section: Introductionunclassified